(untitled) (Journal Of Educational and Psychological Researches, 2015)
Sought Current search to know the concepts of modern literature theoretical educational, psychological and social are thinking double and tolerance and the definition of them in the theoretical frameworks of religious, social and psychological to clarify their role in life in general and in university life private and to understand their respective roles in the promotion of the other, and research has included a chapter first to identify the importance and the objectives and terms Search in detail, and a chapter of a second frameworks and theoretical literature of concepts ranging from religious heritage in Islam and other religions, especially the concept of tolerance, then look at social, psychological and cultural of the two was deeply theoretical, and the final chapter of a conclusion about the commonalities between the two concepts negatively and positively, and how it can be mutually reinforcing the role of the other in the general people then university students, as the base concept of tolerance overshadowed heavily on achieving this role in the reinforcement of the depth of the concept religiously, socially and become arms tolerance feature and human value a great high-Semitism is possessed of the keys double think Baijah and beguile and high capacity to handle negotiation and arms with all conditions difficult, and it was to clarify the role of the university its facilities are all in the upbringing and education and inculcating a culture of tolerance among students and their contribution to deep in the nature of thinking normal free-positive creative as thinking double serve the community in the circumstances experienced by the day, and ended with the researcher’s recommendations and proposals of several serving the area is clear and significant.